2019
DOI: 10.1080/15384101.2019.1632135
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-422a functions as a tumor suppressor in non-small cell lung cancer through SULF2-mediated TGF-β/SMAD signaling pathway

Abstract: MicroRNAs (miRNAs) have been demonstrated to participate in a variety of human cancers by functioning as post-transcriptional regulators of oncogenes or antioncogenes including non-small cell lung cancer (NSCLC). The aim of the current study was to identify the role of miR-422a in NSCLC via sulfatase 2 (SULF2) to further elucidate the mechanism of NSCLC. Initially, the expression of miR-422a and SULF2 was determined in NSCLC tissues and cells. The role of miR-422a in NSCLC was identified in relation with a miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In bladder cancer, Li et al draw a conclusion that miR-1298 serves a tumor suppressor by suppressing tumor cell proliferation, migration and invasion [32]. In the tumor progression of NSCLC, some aberrant miRNAs have important functional roles by regulating tumor cell processes, and have been determined as potential therapeutic targets [33][34][35]. Considering the dysregulation of miR-1298 in NSCLC, this study further explored its biological function in tumor progression.…”
Section: Discussionmentioning
confidence: 90%
“…In bladder cancer, Li et al draw a conclusion that miR-1298 serves a tumor suppressor by suppressing tumor cell proliferation, migration and invasion [32]. In the tumor progression of NSCLC, some aberrant miRNAs have important functional roles by regulating tumor cell processes, and have been determined as potential therapeutic targets [33][34][35]. Considering the dysregulation of miR-1298 in NSCLC, this study further explored its biological function in tumor progression.…”
Section: Discussionmentioning
confidence: 90%
“…Some reports have also shown that oncomir miR-21 downregulates hMSH2 gene expression by targeting the 3 untranslated region of its mRNA [45], and that miR-155 can significantly downregulate hMSH2, hMSH6, and hMLH1 [46], while others have suggested that miRNAs play an important role in modulating cell cycle progression by targeting hMSH2 in lung cancer [42]. Although there are reports suggesting a relationship between the MMR mechanism and miRNA profiles [41,43,44,46], the underlying molecular mechanism by which tobacco smoke carcinogens induce miRNA deregulation and affect the expression profiles of mismatch repair genes, particularly in lung and head and neck cancer, is not yet known.Here, we attempt to explore whether NNK affects the expression of small regulatory molecules, such as known miRNA markers, previously associated with upper aerodigestive tract malignancies [47][48][49][50][51][52][53][54] that may directly or indirectly be involved in the regulation for MMR expression phenotypes. Understanding the molecular changes induced by various risk factors, such as tobacco smoke, which promote the development and progression of cancer, will help to develop new diagnostic and therapeutic approaches [55,56], leading to optimization of their management.…”
mentioning
confidence: 99%
“…Here, we attempt to explore whether NNK affects the expression of small regulatory molecules, such as known miRNA markers, previously associated with upper aerodigestive tract malignancies [47][48][49][50][51][52][53][54] that may directly or indirectly be involved in the regulation for MMR expression phenotypes. Understanding the molecular changes induced by various risk factors, such as tobacco smoke, which promote the development and progression of cancer, will help to develop new diagnostic and therapeutic approaches [55,56], leading to optimization of their management.…”
mentioning
confidence: 99%
“…miR-422a negatively modulates the EGFR/MEK/ERK signaling pathway by targeting the mediator complex subunit (Med19) (44). Additionally, miR-422a serves as a tumor suppressor through the SULF2-mediated TGF-β/SMAD signaling pathway in non-small cell lung cancer (45). Furthermore, miR-422a inhibits the PI3K/AKT pathway by directly targeting PIK3CA and AKT1 in glioma and colorectal cancer, respectively (14,46).…”
Section: Discussionmentioning
confidence: 99%